Ergonomics To Go: Designing The Mobile Workspace. Issue 11 (2nd November 2018) - Janneck, Monique; Jent, Sophie; Weber, Philip; Nissen, Helge
ABSTRACT: The workplace is becoming increasingly mobile, as more and more employees regularly work from their home office, spend a lot of time travelling, work on-site at their customers' place, and use laptops and mobile devices such as smartphones and tablets instead of classical desktop computers. However, while research and checklists on how to create an ergonomic office are readily available, less is known about how the 'mobile workplace' should be designed to reduce strains and stress resulting from unfavourable workplace conditions, non-ergonomic equipment or devices, extensive travelling, or work-home interference. In this paper we present the results of an empirical study on the ergonomic requirements of mobile workers. Based on this, we present the 'Ergonomics Coach', a prototype of an online coaching application with helpful information and exercises adapted to the mobile workplace.